STRATEGI KOMUNIKASI PEMASARAN TERPADU TELAGA KUSUMA KARANGANYAR DALAM MENINGKATKAN KUNJUNGAN WISATAWAN: Komunikasi Pemasaran, Integrated Marketing Communication, Telaga Kusuma, Desa Wisata, Karanganyar - Indarti, Helga Woro; Hindra Hastuti, Nurnawati; Widiyowati, Widiyowati (Solidaritas, 2024)
Currently there are 1073 villages that can be developed into tourist villages. This tourist village concept is also used by Karanganyar district to develop the economic sector by involving several villages as tourist villages. One of them is Jumantono sub-district with the Telaga Kusuma tourist village. Telaga Kusuma Agrotourism and Waterpark is one of the newest tourist attractions in Karanganyar Regency, which is located in nggulrejo village, Jumantono District. This research was conducted to reveal matters related to the Telaga Kusuma Karanganyar Integrated Marketing Communication Strategy efforts to increase tourist visits. The type of research used is qualitative with a case study approach which focuses on how the existing Marketing Communication Strategy at Telaga Kusuma increases tourist visits. Data collection in this research was obtained through interviews, observation, documentation with informants. Based on research that has been carried out, the integrated marketing communications strategy at Telaga Kusuma Karanganyar includes planning, implementation and evaluation of integrated marketing communications. Telaga Kusuma has a Marketing Team which doubles as Public Relations. The Telaga Kusuma marketing team has a very important role in promoting Telaga Kusuma tourism which makes Telaga Kusuma have a list of visitors that is never empty. One of the efforts made is by implementing several marketing communication models such as Word of Mouth and Social Media.